Does firm size influence innovative water management responses in the hotel sector? - Kasim, Azilah; Dzakiria, Hisham; Ahmad, Rozila (American Scientific Publishers, 2017)
This paper looks at the influence of firm size on innovative water management responses among hotels. A quantitative survey was conducted in three major tourism destinations i.e., Langkawi, Penang and Kuala Lumpur. Using personally assisted questionnaire, the survey managed to collect 208 completed questionnaires out of the intended sample size of 342. Results showed that size does influence hotel’s environmental response as big hotels are more informed and responsive about innovative water management compared to their smaller and medium size counterparts. This effectively highlight that small and medium size hotels, despite being higher in number, may still be ‘doing business as usual’ due to lack of awareness and understanding on the importance of innovative water management. Several implications are discussed at the end of the paper.